Modelos e algoritmos para a otimização do planejamento da produção de grãos eletrofundidos - Luche, José Roberto Dale (2011)
The number of successful applications that use optimization models has followed the evolution of the computers, as much in hardware, with more powerful machines, as in software, with more intelligent algorithms. Due to importance of the modeling as a decision support tool, much effort has been made to mathematically describe systems of interest and devise techniques for solving such models. This work presents a detailed description of the operations involved in production planning and control of the electrofused grain industry and proposes the use of exact and heuristic methods to support decisions in such activities, particularly in production scheduling. Several visits were made to companies in this sector and a case study was carried out one of these companies in order to formulate alternatives to increase productivity and improve customer service. Optimizing the production scheduling of electrofused grains is not a simple task mainly because of the scale of the equipment setup times, the diversity of the products, and the narrow orders due dates. Based on the case study, mixed linear programming models that combine known models of process selection and single-stage lot sizing were developed, and a constructive heuristic, local search variants, and a GRASP algorithm were proposed to solve one of the models. Computational results with a real instance and randomly generated instance sets show that the exact methods as well as the heuristics can produce as good or better production scheduling than the ones currently employed by the studied company